Dropshipping System In The Practice Of Buying And Selling: A Review From The Perspective Of Islamic Business Ethics - Chairani Firstia Rizal; Muahammad Iqbal Bin Ahmadi Salim Bafadhal; Rafiqi Rafiqi (Cita konsultindo, 2024)
This research aims to determine the mechanisms, obstacles and ethics of Islamic business in buying and selling in the dropshipping system. The research method used is qualitative. The data source used in this research is primary. The data collection techniques used in this research areobservation, interviews and documentation. The results of this study indicate that (1) The mechanism of the dropshipping system carried out by the dropshipper is to take or order goods from trusted suppliers and provide the buyer's identity then the supplier will send directly to the buyer. (2) Common obstacles faced by dropshippers when buying and selling are goods sent by suppliers experiencing delays, so buyers have to wait until they arrive at their destination, and the estimated delivery time is not appropriate. Another obstacle is that some buyers have no news or have disappeared. This occurs when transactions are Cash On Delivery (COD) in nature, business actors prefer cash transfer transactions or mobile banking. (3) The dropshipping system in terms of buying and selling practices in terms of Islamic business ethics has met the qualifications in Islamic business ethics, especially in honesty and good faith. Islamic business ethics provide provisions that business people must know, understand and also carry out ethical principles in doing business, such as monotheism (oneness), fairness, honesty and responsibility. In terms of production, distribution, exchange of goods or services, Islamic business ethics are good business practices. Activities based on good ethics can ensure business activities run smoothly and in balance because ethics can determine how well a job is done.